If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8u + -30 = -6(u + 7) Reorder the terms: -30 + -8u = -6(u + 7) Reorder the terms: -30 + -8u = -6(7 + u) -30 + -8u = (7 * -6 + u * -6) -30 + -8u = (-42 + -6u) Solving -30 + -8u = -42 + -6u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '6u' to each side of the equation. -30 + -8u + 6u = -42 + -6u + 6u Combine like terms: -8u + 6u = -2u -30 + -2u = -42 + -6u + 6u Combine like terms: -6u + 6u = 0 -30 + -2u = -42 + 0 -30 + -2u = -42 Add '30' to each side of the equation. -30 + 30 + -2u = -42 + 30 Combine like terms: -30 + 30 = 0 0 + -2u = -42 + 30 -2u = -42 + 30 Combine like terms: -42 + 30 = -12 -2u = -12 Divide each side by '-2'. u = 6 Simplifying u = 6
| -3rs(2r^2s+12t-7)= | | -2x-66=62-10x | | 4(x-7)=7x-13 | | K-15=-40 | | -55-2x=-5x+17 | | -5(1+4x)=195 | | 2n+8=3(n-9) | | 3y+18=-6(y-9) | | -31-7x=17-11x | | -3x+5(-9+4x)=-x-4 | | (4)*(3x+12)=64 | | -76+7x=104-2x | | 12x-25=7x+35 | | -4x-14=-7x+12 | | 5x-2(-2x+19)=-83 | | 3(1x+5)=42 | | 8x-68=77+4x | | 3x-6(1+x)=-9x+9 | | 3b-50=4b-74 | | -124+12x=5x+86 | | 9x^2+4x+87=180 | | 6a+70=a | | 8x-151=49-2x | | 5x+3x-9=15 | | 3m^2-7m-40=0 | | -126+9x=39-2x | | -12-2x=-20 | | -93+4x=-6x+107 | | 4y=6y-12 | | 7x^2+3x+88=180 | | -x-21=-5x+19 | | -2(-4+7x)+8x=3 |